Semiconductors Synthesis, Properties and Applications - Pech-Canul, Martin I.; Ravindra, Nuggehalli M. (Springer International Publishing : Imprint: Springer, 2019)
This book is a practical guide to optical, optoelectronic, and semiconductor materials and provides an overview of the topic from its fundamentals to cutting-edge processing routes to groundbreaking technologies for the most recent applications. The book details the characterization and properties of these materials. Chemical methods of synthesis are emphasized by the authors throughout the publication. Describes new materials and updates to older materials that exhibit optical, optoelectronic and semiconductor behaviors; Covers the structural and mechanical aspects of the optical, optoelectronic and semiconductor materials for meeting mechanical property and safety requirements; Includes discussion of the environmental and sustainability issues regarding optical, optoelectronic, and semiconductor materials, from processing to recycling.